If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9+2x^1=3x^1-2
We move all terms to the left:
9+2x^1-(3x^1-2)=0
We do not support expression: x^1
| 2x(x^2+2x-5)=0 | | -7d+d+-3d+2d=7 | | -2x+9-7x+9=27 | | 3d-2(-8+5d)=-3d-3d | | x+(-16)=-38 | | 5p5p=6p-2 | | 3+5p=6p+1-3p+6 | | —8—n=4—4n | | 1b-4+8b=21 | | -4=x5 | | 9.50n+1.25(3n+2)=68.75 | | -10x-15x-3x=8 | | -16=9x-7 | | -5x=16x-7 | | 9.50n+(1.25*3n)+2=68.75 | | 14=5+x/2 | | 244=14b+6 | | 11r-5r+2r+3r-8r=18 | | z^2+14z+28=0 | | 1+8x+9=-202x | | (h/4)^2*h=108 | | 6/2+8x/2=5x | | 3r-3=2r-2 | | 3x+6-22=0 | | z+37–8=4 | | 10p+p+2p-4p=18 | | 8(y+2)=10y-2y+16 | | 9.50n+(3n*1.25)+2=68.75 | | k+4=44 | | 36-2x=-x-34 | | 2^(x+3)=3x+8 | | (3x+6)^2=22 |